2022
DOI: 10.36740/wlek202207106
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Parietal Foramen and Its Relations to the Calvarial Landmarks: A Cross-Sectional Cadaveric Study

Abstract: The aim: Estimate the prevalence of the parietal foramen in the adult human skulls of Ukrainian origin, and study its morphology and relationships to main anatomical landmarks of the skull. Materials and methods: A cross-sectional observational study of PF was conducted with 42 random cadaveric adult human skull roofs (calvaria) collected from the laboratory and museum of Human Anatomy Department, Kharkiv National Medical University, Ukraine. The patency and the length of the PF canal were determined, and PF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In the literature, PF is often reported to be absent, single or double [2,3,15,18,21,22,29]. In some studies, it was noted that this foramen may be 3 or more in number [4,8,9,17,26,30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, PF is often reported to be absent, single or double [2,3,15,18,21,22,29]. In some studies, it was noted that this foramen may be 3 or more in number [4,8,9,17,26,30].…”
Section: Resultsmentioning
confidence: 99%
“…Murlimanju et al [17], Shantharam and Manjunath [21], and Halagatti and Sagar [9] agreed that similar to the results of our study, PF is located between the middle and posterior 1/3 of the parietal bones. Shmarhalov et al [22] reported that the most common location of PF was at the side of the sagittal suture, mid of the distance between the vertex and lambda. The size, presence, content, and topography of PFs are variable.…”
Section: Morphometric Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Краніометрія склепіння черепа, завжди викликала зацікавленість великої кількості науковцівморфологів, ця ділянка є вкрай важливою з позиції виконання безлічі нейрохірургічних втручань при проведені доступів до внутрішньочерепних структур [1][2][3][4]. Тім'яна кістка як одна з найбільших структур мозкового відділу черепа має значну залежність від встановленого краніотипу, при цьому існують певні діапазони змін основних лінійних параметрів, що підтверджується дослідженнями ряду авторів [5][6][7][8][9][10].…”
Section: краніометрична характеристика тім'яних кісток склепіння чере...unclassified
“…The variability of the shape of the organ is one of the manifestations of its individual anatomical variability. One of the ways to determine the shape of an organ is to evaluate the ratio of its linear dimensions [17,21,30]. Magnetic resonance imaging and other modern neuroimaging research methods make it possible to establish the morphological features of organs during life, while preserving their natural position.…”
Section: Introductionmentioning
confidence: 99%